Antifungal effect of α-pinene alone and in association with antifungals against Candida albicans strains (Research, Society and Development, 2022)
Caused by fungi of the genus Candida spp., candidiasis is reported as a public health problem, causing superficial and systemic infections. The increase in isolated resistant strains and the high toxicity of conventional antifungal agents have stimulated the search for alternatives to this scenario, such as bioproducts or isolated compounds, such as terpenes. Thus, it is important to investigate the antifungal activity of α-pinene alone and in association with antifungals against strains of Candida albicans. For this, the Minimum Inhibitory Concentration (MIC) and the Minimum Fungicide Concentration (MFC) were determined by the technique of microdilution in broth of the isolated terpene and the association assay (checkerboard) between α-pinene and antifungals, such as fluconazole and amphotericin. B. The α-pinene had a MIC between 128 and 512 µg/mL and the CFM had the same MIC values ​​against the 8 strains tested. The other concentrations could not determine the CFM, due to the fungal growth being greater than or equal to MICx4 (test limit). In the association trial, the interaction between α-pinene and fluconazole was indifferent, whereas the combinations between α-pinene with amphotericin B and nystatin obtained synergistic effects. Thus, this study strengthens α-pinene as a promising antifungal agent, as it exhibited strong inhibitory activity against Candida albicans strains, with a fungicidal nature. Additionally, it may be used in association with polyene derivatives (amphotericin B or nystatin) as an alternative in the treatment of candidiasis. It should be noted that more studies need to be carried out on the mechanism of action and toxicity of this compound.